Molecular adaptation to neoadjuvant immunotherapy in triple-negative breast cancer - Denkert, Carsten; Schneeweiss, Andreas; Rey, Julia; Karn, Thomas; Hattesohl, Akira; Weber, Karsten E.; Rachakonda, Sivaramakrishna; Braun, Michael; Huober, Jens; Jank, Paul; Sinn, Peter; Zahm, Dirk-Michael; et al. (Cell reports. Medicine, 2024)
Therapy-induced molecular adaptation of triple-negative breast cancer is crucial for immunotherapy response and resistance. We analyze tumor biopsies from three different time points in the randomized neoadjuvant GeparNuevo trial (NCT02685059), evaluating the combination of durvalumab with chemotherapy, for longitudinal alterations of gene expression. Durvalumab induces an activation of immune and stromal gene expression as well as a reduction of proliferation-related gene expression. Immune genes are positive prognostic factors irrespective of treatment, while proliferation genes are positive prognostic factors only in the durvalumab arm. We identify stromal-related gene expression as a contributor to immunotherapy resistance and poor therapy response. The results provide evidence from clinical trial cohorts suggesting a role for stromal reorganization in therapy resistance to immunotherapy and in the generation of an immune-suppressive microenvironment, which might be relevant for future therapy approaches targeting the tumor stroma parallel to immunotherapy, such as combinations of immunotherapy with anti-angiogenic therapy.
Online verfügbar: 19. November 2024, Artikelversion: 19. November 2024
Gesehen am 28.04.2025